The Influence of CEO Education and Voluntary Carbon Disclosure on Capital Structure: Empirical Evidence from Indonesia - Setyaningrum, Lani Mara; Djuminah, Djuminah (JURNAL MANAJEMEN MOTIVASI, 2025)
This study investigates the impact of CEO education on capital structure, with voluntary carbon disclosure (VCD) as a mediating variable. Data from 308 high-emission firms in Indonesia (2021–2023) were analyzed using path analysis. Results show CEO education level significantly influences VCD, while discipline does not. VCD improves capital structure by increasing investor trust and mediates the effect of education level on capital structure. Findings support Upper Echelon and Signaling theories, emphasizing the strategic role of CEO characteristics in promoting sustainability and optimizing funding decisions in environmentally sensitive sectors, particularly in the pursuit of sustainable development and carbon transparency goals.